The endocrine and metabolic characteristics of a large Bardet-Biedl syndrome clinic population - Mujahid, S; Hunt, KF; Cheah, YS; Forsythe, E; Hazlehurst, JM; Sparks, K; Mohammed, S; Tomlinson, JW; Amiel, SA; Carroll, PV; Beales, PL; Huda, MSB; et al. (Oxford University Press, 2018)
Bardet-Biedl syndrome (BBS) is a rare autosomal recessive disorder in which previous reports have described obesity and a metabolic syndrome.Describe the endocrine and metabolic characteristics of a large BBS population compared with matched controls.Case-control.Hospital clinic.A clinical/genetic diagnosis of BBS.None.Prevalence of metabolic syndrome.One hundred and fifty-two subjects were studied. Eight-four (55.3%) were male and mean (±SD) age was 33.2±1.0 years. Compared with age, gender and BMI matched controls, fasting glucose and insulin levels were significantly higher in BBS subjects (glucose: BBS: 5.2±1.2mmol/l vs control 4.9±0.9mmol/l, p=0.04; insulin: BBS: 24.2±17.0pmol/l vs control 14.2±14.8pmol/l, p<0.001). Serum triglycerides were significantly higher in BBS subjects (2.0±1.2mmol/l) compared with controls (1.3± 0.8mmol/l p<0.001) but total cholesterol/HDL/LDL were similar in both groups. Systolic blood pressure was higher in the BBS group (BBS 135±18 mmHg vs controls 129±16mmHg (p=0.02). Alanine transaminase (ALT) was raised in 34 (26.8%) BBS subjects, compared to 5 (8.9%) controls (p=0.01). The presence of a metabolic syndrome, using IDF criteria, was significantly higher in the BBS group (54.3%) compared to controls (26% p<0.001). Twenty-six (19.5%) of BBS males were hypogonadal (serum testosterone 9.9±5.3 mmol/l) but significant pituitary abnormalities were uncommon. Subclinical hypothyroidism was present in 24/125 (19.4%) patients with BBS compared with 3/65 (4.6%) controls (p=0.01).Insulin resistance and the metabolic syndrome are increased in adult BBS compared with matched controls. Increased subclinical hypothyroidism in the BBS cohort is a novel finding that needs further investigation.